Ensure the quality of scientific research using scientific virtual library - Thana khalf; hassan Gameg; lamia maola (University of Science and Technology, Yemen, 2014)
Abstract Search aims to introduce the concept of scientific research and standards in the  total quality and the concept of the Iraqi scientific virtual libraries and how to search the electronic sources and the analysis and use of virtual reality for the library in the Iraqi scientific research faculty of the Institute of Directors / Rusafa. Been using the survey method field to prepare faculty to participate in Iraq's virtual library, where and distributed them resolution No. (1) and contain the (10) questions related to the subject of scientific research and virtual library and use either the standard measure of scientific research has been the distribution of resolution No. (2) on the heads scientific departments in the administration / Rusafa Institute and included (41) questions. The most important findings of research reference: 1-attention of the Ministry of Higher Education and Scientific Research Library default because of their importance to ensure the quality of scientific research and allow the use of the library for teachers and researchers free of charge. 2-The rate of change in the preparation of scientific research has been positive for the academic year 2010/2011, reaching (%558.3+), which gave indication of the role and importance of scientific virtual library in the provision of electronic resources needed by the researchers in their research. 3-sources of electronic access to information through search and retrieval (abstracts , full-text, keywords, databases, depending on the type of container information) through Iraqi Virtual Science Library. 4-amounted answers ratio (100%) to use technological methods while writing scientific research.   The main proposals are: 1-support and encourage electronic publishing of scientific research in the Arab and international scientific journals. 2-continue to provide electronic environment (Iraqi Virtual Library Scientific) for the development of the potential of the teaching staff and the ability to development and innovation. 3-emphasis on cooperation with the private sector through the development of applied scientific research to be funded by them.Key words: quality standards, scientific research, virtual library, virtual  library science Iraq.